(untitled) (Nepali Media: Issue of Ethics and Sustainability, 2025)
This study uses a descriptive approach to analyze the status of mass communication and journalism in Nepal during FY 2024/25. Despite a growing demand for skilled professionals, journalism student enrollment continues to decline. Traditional media—print, radio, and TV—are stagnating or shutting down, while online outlets are expanding, with 5,126 registered by mid-2025. However, this growth has led to more violations of journalistic ethics and a rise in related court cases. Press freedom remains fragile, with frequent threats and assaults reported by the Press Council Nepal (PCN) and the Federation of Nepali Journalists (FNJ). The FNJ’s membership dropped from over 13,000 to around 9,340 after purification campaign. Graduates are increasingly reluctant to enter journalism due to limited job opportunities. Policy developments included the enactment of the Public Service Broadcasting Act and the Security Printing Act, though key reforms like the Media Council Bill and a national advertising policy remain stalled. Provincial legislation exists but lacks consistent implementation. While PCN continues to update the journalists’ code of conduct and offer training and financial support, the overall press freedom situation is concerning. Nonetheless, increased academic research and publications reflect ongoing engagement in the field.